PENGARUH SISTEM PENGENDALIAN KEUANGAN DAERAH DENGAN METODE VALUE FOR MONEY TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH (Studi Kasus Pada BPKAD Kota Bengkulu) - Subaeti Subaeti; Weni Susanti; Monalisa Sianturi (LPPM Universitas Bina Insan, 2020)
This study aims to determine how much influence the regional financial control system has on the economy, efficiency, effectiveness on the quality of regional financial reports at BPKAD Bengkulu City. The research method uses data quality test, classical assumption test, multiple linear regression analysis, t test, F test, and the coefficient of determination. The results of the calculation obtained a multiple linear regression equation, namely Y = 3.329 + 0.255X1 + 0.588X2 + 0.111X3 + e, from the equation it means that there is a positive influence between the two variables. The coefficient of determination (R²) of 0.863 and Adjusted R Square of 0.852 indicate that the influence of the regional financial control system on the economy, efficiency, effectiveness on the quality of regional financial reports is very strong. Based on the t value obtained in the hypothesis test (t-test), it was obtained X1 with a tcount of 2.379 with a significant value of 0.023, for X2 for tcount of 5.461 with a significant value of 0.000, and for X3 for tcount of 2.332 with a significant value of 0.025, while the t-table value of 1.68830 (tcount> ttable). The hypothesis is accepted or a significant value <0.05. Based on the F value obtained in the hypothesis test (F-test), the Fcount is 75.644> Ftable is 2.87. The hypothesis is accepted or a significant value <0.05. This means that the regional financial control system with economy, efficiency, effectiveness has a significant positive effect on the quality of regional financial reports at BPKAD Bengkulu.